Bioactivity of volatile organic compounds produced by Pseudomonas tolaasii - Lo Cantore, Pietro; Giorgio, Annalisa; Iacobellis, Nicola S. (Frontiers in Microbiology, 2015)
Pseudomonas tolaasii is the main bacterial pathogen of several mushroom species. In this paper we report that strains of P. tolaasii produce volatile substances inducing in vitro mycelia growth inhibition of Pleurotus ostreatus and P. eryngii, and Agaricus bisporus and P. ostreatus basidiome tissue blocks brown discoloration. P. tolaasii strains produced the volatile ammonia but not hydrogen cyanide. Among the volatiles detected by GC-MS, methanethiol, dimethyl disulfide, and 1-undecene were identified. The latter, when assayed individually as pure compounds, led to similar effects noticed when P. tolaasii volatiles natural blend was used on mushrooms mycelia and basidiome tissue blocks. Furthermore, the natural volatile mixture, resulted toxic toward lettuce and broccoli seedling growth. In contrast, pure volatiles showed different activity according to their nature and/or doses applied. Indeed, methanethiol resulted toxic at all the doses used, while dimethyl disulfide toxicity was assessed till a quantity of 1.25 µg, below which it caused, together with 1-undecene ( 10 µg), broccoli growth increase.